Directed block copolymer self-assembly implemented via surface-embedded electrets - Mei-Ling Wu (Nature Portfolio, 2016)
The controlled orientation of block copolymers promises to deliver high resolution patterning for implementation in future nanoscale technologies. Here, the authors use the electric field from charged electrets to induce extremely localised perpendicularly oriented microdomains in polymer thin films.